Hadith #2327 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Imran bin Husain; Matruf bin Tarayf al-Harithi مطرف بن طريف; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Prophet (ﷺ) said: Do not fast one day or two days just before Ramadan except in the case of a man who has been in the habit or observing a fast (on that day); and do not fast until you sight it (the moon). Then fast until you sight it. If a cloud appears on that day (i.e. 29th of Ramadan) then complete the number thirty (days) and then end the fasting: a month consists of twenty-nine days.
Grade: Sahih

Hadith #2483 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Imran bin Husain; Matruf bin Tarayf al-Harithi مطرف بن طريف; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Qatada قتادة (Sunan Abi Dawud)
The Prophet (ﷺ) said: It will turn out that you will be armed troops, one is Syria, one in the Yemen and one in Iraq. Ibn Hawalah said: Choose for me, Messenger of Allah, if I reach that time. He replied: Go to Syria, for it is Allah’s chosen land, to which his best servants will be gathered, but if you are unwilling, go to your Yemen, and draw water from your tanks, for Allah has on my account taken special charge of Syria and its people.
Grade: Sahih

Hadith #2488 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Isma'il bin Zakaria bin Mrh إسماعيل بن زكريا بن مرة; Matruf bin Tarayf al-Harithi مطرف بن طريف; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة (Sunan Abi Dawud)
A woman called Umm Khallad came to the Prophet (ﷺ) while she was veiled. She was searching for her son who had been killed (in the battle) Some of the Companions of the Prophet (ﷺ) said to her: You have come here asking for your son while veiling your face? She said: If I am afflicted with the loss of my son, I shall not suffer the loss of my modesty. The Messenger of Allah (ﷺ) said: You will get the reward of two martyrs for your son. She asked: Why is that so, Messenger of Allah? He repl
Grade: Da'if

Hadith #2800 - Sunan Abi Dawud - al-Bara' bin Azib bin al-Harith; Amir al-Sha'bi عامر الشعبي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Matruf bin Tarayf al-Harithi مطرف بن طريف (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) delivered a sermon to us on the day of sacrifice after the prayer. He said: If anyone prays like our prayer, and sacrifices like our sacrifice, his sacrifice is all right. If anyone sacrifices before the prayer (for ‘Id), that is goat meant for flesh. Abu Burdah b. Niyar stood up and said: Messenger of Allah, I swear by Allah, I sacrificed before I went for prayer. I thought it was the day of eating and drinking; so I made haste, and ate myself, and supplied flesh
Grade: Sahih

Hadith #2946 - Sunan Abi Dawud - Abu Mas'ud al-Badri; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Matruf bin Tarayf al-Harithi مطرف بن طريف; Uthman bin Muhammad (Sunan Abi Dawud)
The Prophet (ﷺ) appointed a man of Azd called Ibn al-Lutbiyayah (to collect sadaqah). The narrator Ibn al-Sarh said: (He appointed) Ibn al-Utbiyyah to collect the sadaqah. When he returned he said: This is for you and this was given to me as present. So the Prophet (ﷺ) stood on the pulpit, and after praising and extolling Allah he said: What is the matter with a collector of sadaqah. We send him (to collect sadaqah), and when he return he says: This is for you and this is a present which was
Grade: Sahih

Hadith #2982 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Abu Ja'far al-Razi أبو جعفر الرازي; Ali ibn Abi Talib; Matruf bin Tarayf al-Harithi مطرف بن طريف; Yahya bin Abi Bkyr يحيى بن أبي بكير واسمه نسر (Sunan Abi Dawud)
Yazid ibn Hurmuz said that when Najdah al-Haruri performed hajj during the rule of Ibn az-Zubayr, he sent someone to Ibn Abbas to ask him about the portion of the relatives (in the fifth). He asked: For whom do you think? Ibn Abbas replied: For the relatives of the Messenger of Allah (ﷺ). The Messenger of Allah (ﷺ) divided it among them. Umar presented it to us but we found it less than our right. We, therefore returned it to him and refused to accept it.
Grade: Sahih

Hadith #2990 - Sunan Abi Dawud - Amir al-Sha'bi عامر الشعبي; Matruf bin Tarayf al-Harithi مطرف بن طريف; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Mujja’ah went to the Prophet (ﷺ) asking him for the blood-money of his brother whom Banu Sadus from Banu Dhuhl had killed. The Prophet (ﷺ) said: Had I appointed blood-money for a polytheist, I should have appointed it for your brother. But I shall give you compensation for him. So the Prophet (ﷺ) wrote (a document) for him that he should be given a hundred camels which were to be acquired from the fifth taken from the polytheists of Banu Dhuhl. So he took a part of them, for Banu Dhuhl e
Grade: Da'if

Hadith #3864 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Imran bin Husain; Matruf bin Tarayf al-Harithi مطرف بن طريف; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Prophet (ﷺ) sent a physician to Ubayy (ibn Ka’b), and he cut his vein.
Grade: Sahih

Hadith #4073 - Sunan Abi Dawud - Aisha bint Abi Bakr; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Matruf bin Tarayf al-Harithi مطرف بن طريف; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة (Sunan Abi Dawud)
I saw the Messenger of Allah (ﷺ) at Mina giving sermon on a mule and wearing a red garment, while Ali was announcing.
Grade: Sahih

Hadith #4454 - Sunan Abi Dawud - al-Bara' bin Azib bin al-Harith; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Matruf bin Tarayf al-Harithi مطرف بن طريف (Sunan Abi Dawud)
A similar tradition has also been transmitted by al-Sha’bi through a different chain of narrators.
Grade: Da'if

Hadith #4707 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Imran bin Husain; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Matruf bin Tarayf al-Harithi مطرف بن طريف; Yazid bin Abi Yazid, al-Rashk يزيد بن أبي يزيد الضبعي الرشك (Sunan Abi Dawud)
Ubayy b. Ka’b told me that the Messenger of Allah (May peace be upon him) said : Al-khidr saw a youth playing with boys. He took him by his head and uprooted it. Moses then said : Hast thou slain an innocent person who had slain none.
Grade: Sahih

Hadith #4756 - Sunan Abi Dawud - Abu Dharr al-Ghaffari; Matruf bin Tarayf al-Harithi مطرف بن طريف; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
I heard the Prophet (ﷺ) say: There has been no Prophet after Noah who has not warned his people about the antichrist (Dajjal), and I warn you of him. The Messenger of Allah (ﷺ) described him to us, saying: Perhaps some who have seen me and heard my words will live till his time. The people asked: Messenger of Allah! what will be the condition of our hearts on that day? Like what we are today? He replied: Or better.
Grade: Hasan

Hadith #4757 - Sunan Abi Dawud - Abu Dharr al-Ghaffari; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Matruf bin Tarayf al-Harithi مطرف بن طريف; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
The Messenger of Allah (May peace be upon him) stood among the people and praised Allah in a way which is worthy of him, and mentioned the Antichrist (Dajjal), saying : I warn you of him, and there has been no prophet who has not warned his people about him, and Noah also warned his people about him. But I tell you about him a word which no Prophet had told his people : you should know that he will be blind in one eye, and Allah is not blind is one eye.
Grade: Sahih

Hadith #4804 - Sunan Abi Dawud - al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Matruf bin Tarayf al-Harithi مطرف بن طريف; Sa'id bin Yazid bin Muslima سعيد بن يزيد بن مسلمة الأزدي القصير (Sunan Abi Dawud)
A man came and praised ‘Uthman in his face, al-Miqdad b. Al-Aswad took dust and threw it on his face, saying : The Apostle of Allah (ﷺ) said : When you see those who are given to praising people, throw dust in their faces.
Grade: Sahih